Another look at influences of the Madden-Julian Oscillation on the wintertime East Asian weather - He, Jinhai; Lin, Hai; Wu, Zhiwei (Journal of Geophysical Research, 2011)
As one of the major predictability sources on an intraseasonal time scale, the Madden‐Julian Oscillation (MJO) exerts a profound influence on the subseasonal forecast of the East Asian (EA) surface air temperature (SAT) and precipitation. In this study we examine the direct link of the MJO with the EA SAT and precipitation and its dynamical mechanism. To represent the MJO, we perform an empirical orthogonal function (EOF) analysis on pentad outgoing longwave radiation (OLR) over (20°S−20°N, 60°E−150°W). The EOF1 mode is mostly characterized by a single convection center near the maritime continent (90°−150°E), whereas the EOF2 mode has an east‐west dipole structure with enhanced convection over the eastern Indian Ocean and suppressed convective activities over the tropical western Pacific. At the same pentad of a positive EOF1 phase, large areas of cold anomalies with reduced precipitation emerge in the EA region north of 20°N and persist through two pentads later. At the same pentad of a positive EOF2 phase, SAT and precipitation exhibit a zonal dipole pattern with cold and dry anomalies covering the EA region west of 120°E and warm and wet anomalies to the east. These dipole anomalies in SAT and precipitation systematically move eastward in the next two pentads. A linearized global primitive equation model is utilized to assess the cause of the intraseasonal variability in SAT and precipitation over East Asia associated with the tropical heating of the MJO. The model responses to heating sources that mimic the EOF1 and EOF2 OLR patterns match well the general features of the observed circulation anomalies. Under forcing of a positive phase of the EOF1 pattern, strengthened local Hadley cell or monsoon circulations within (90°E−150°E) are reproduced, with anomalous northerly winds and dry anomalies prevailing in the lower troposphere over East Asia. The processes that influence East Asia are mainly associated with intraseasonal changes in local Hadley circulation and the Northern Hemisphere branch of the equatorially trapped Rossby wave gyres forced by the MJO heating.